Kanglexin, a novel anthraquinone compound, protects against myocardial ischemic injury in mice by suppressing NLRP3 and pyroptosis - Bian Yu; Li Xin; Pang Ping; Hu Xue-ling; Yu Shu-ting; Liu Yi-ning; Li Xin; Wang Ning; Wang Jin-hui; Xiao Wei; Du Wei-jie; Yang Bao-feng (Acta Pharmacologica Sinica; Vol 41, No 3 (March 2020): Acta Pharmacologica Sinica, 2020)
Pyroptosis is a form of inflammatory cell death that could be driven by the nucleotide-binding oligomerization domain-like receptor family pyrin domain-containing 3 (NLRP3) inflammasome activation following myocardial infarction (MI). Emerging evidence suggests the therapeutic potential for ameliorating MI-induced myocardial damages by targeting NLRP3 and pyroptosis. In this study, we investigated the myocardial protection effect of a novel anthraquinone compound (4,5-dihydroxy-7-methyl-9,10-anthraquinone-2-ethyl succinate) named Kanglexin (KLX) in vivo and in vitro. Male C57BL/6 mice were pre-treated either with KLX (20, 40 mg· kg−1per day, intragastric gavage) or vehicle for 7 consecutive days prior to ligation of coronary artery to induce permanent MI. KLX administration dose-dependently reduced myocardial infarct size and lactate dehydrogenase release and improved cardiac function as compared to vehicle-treated mice 24 h after MI. We found that MI triggered NLRP3 inflammasome activation leading to conversion of interleukin-1β (IL-1β) and IL-18 into their active mature forms in the heart, which could expand the infarct size and drive cardiac dysfunction. We also showed that MI induced pyroptosis, as evidenced by increased DNA fragmentation, mitochondrial swelling, and cell membrane rupture, as well as increased levels of pyroptosis-related proteins, including gasdermin D, N-terminal GSDMD, and cleaved caspase-1. All these detrimental alterations were prevented by KLX. In hypoxia- or lipopolysaccharide (LPS)-treated neonatal mouse ventricular cardiomyocytes, we showed that KLX (10 μM) decreased the elevated levels of terminal deoxynucleotidyl transferase dUTP nick end labeling- and propidium iodide-positive cells, and pyroptosis-related proteins. We conclude that KLX prevents MI-induced cardiac damages and cardiac dysfunction at least partly through attenuating NLRP3 and subsequent cardiomyocyte pyroptosis, and it is worthy of more rigorous investigations for its potential for alleviating ischemic heart disease.